Women’s Political Participation - Video of Researcher and some Women in FGD in Enugu - Ademola-Adeoye, Feyisayo (Locating the Albatross in Women's Political Participation in Sub-Saharan Africa, 2021)
Video on pilot study recorded in Enugu, Enugu State
Keywords: Women; Sub-Saharan Africa; Political rights; Political participation; Structural Barriers; Political Barriers; Politics